Chapter 7 The Digitally Natural Hypomediacy and the "Really Real" in Game Design - Malaby, Thomas M. (Taylor & Francis, 2023)
This chapter is a consideration of how we may approach the question of remediation in digital games, suggesting that we recognize how digital game remediation incorporates what are often more obvious elements from analogue game design into the more implicit infrastructure of digital contexts. Additionally, such remediation often exhibits "hypomediacy," the denial of game design mediation, with important consequences for how useful digital games have become for institutional projects and their claims about reality. Anthropological treatments of ritual, and specifically how the engagement of audiences with ambiguous performances produces the real for participants, point toward important implications for digital games, where the infrastructural game elements may underwrite a similar process of reality construction through player performance. My overall suggestion is that when we give the cultural form of game its due (as we have for ritual and bureaucracy) - that is, when we incorporate a robust consideration of game features into our analyses - we will be in a better position to illuminate the ways in which our engagement with digital infrastructure is fraught with claims about the real.